Search for the lepton-flavour violating decays B0(s)→ e± [mu][minus-plus] - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; De Cian, Michel; Comerma-Montells, Albert; Dziewiecki, Michal; Esen, Sevda; Gerick, David; Grabowski, Jascha; Grünberg, Oliver; et al. (Journal of high energy physics, 2018)
A search for the lepton-flavour violating decays B s 0 → e±μ∓ and B0 → e±μ∓ is performed based on a sample of proton-proton collision data corresponding to an integrated luminosity of 3 fb−1, collected with the LHCb experiment at centre-of-mass energies of 7 and 8 TeV. The observed yields are consistent with the background-only hypothesis. Upper limits on the branching fraction of the B s 0 → e±μ∓ decays are evaluated both in the hypotheses of an amplitude completely dominated by the heavy eigenstate and by the light eigenstate. The results are @B(B0s→e±μ∓)<6.3(5.4)×10−9@@B(Bs0→e±μ∓)<6.3(5.4)×10−9 \frac{@}{@}\mathrm{\mathcal{B}}\left(B_s^0→ {e}^{± }{μ}^{\mp}\right)<6.3(5.4)× 1{0}^{-9} and @@B(B0s→e±μ∓)<7.2(6.0)×10−9@@B(Bs0→e±μ∓)<7.2(6.0)×10−9 \frac{@}{@}\mathrm{\mathcal{B}}\left(B_s^0→ {e}^{± }{μ}^{\mp}\right)<7.2(6.0)× 1{0}^{-9} at 95% (90%) confidence level, respectively. The upper limit on the branching fraction of the B0 → e±μ∓ decay is also evaluated, obtaining @@B(B0→e±μ∓)<1.3(1.0)×10−9@@B(B0→e±μ∓)<1.3(1.0)×10−9 \frac{@}{@}\mathrm{\mathcal{B}}\left(B^0→ {e}^{± }{μ}^{\mp}\right)<1.3(1.0)× 1{0}^{-9} at 95% (90%) confidence level. These are the strongest limits on these decays to date. Open image in new window